Recursive symmetries for geometrically complex and materially heterogeneous additive manufacturing. (December 2016) - Bader, Christoph; Oxman, Neri
Abstract: We present a generative method for the creation of geometrically complex and materially heterogeneous objects. By combining generative design and additive manufacturing, we demonstrate a unique form-finding approach and method for multi-material 3D printing. The method offers a fast, automated and controllable way to explore an expressive set of symmetrical, complex and colored objects, which makes it a useful tool for design exploration and prototyping. We describe a recursive grammar for the generation of solid boundary surface models suitable for a variety of design domains. We demonstrate the generation and digital fabrication of watertight 2-manifold polygonal meshes, with feature-aligned topology that can be produced on a wide variety of 3D printers, as well as post-processed with traditional 3D modeling tools. To date, objects with intricate spatial patterns and complex heterogeneous material compositions generated by this method can only be produced through 3D printing. Highlights: Proposes a generative system capable of creating of a diverse set of complex objects. Shows dissimilarity of generated objects by a spectral method. Shows how generated objects can be fabricated with multi-material 3d-printing.